Trailing-edge noise: development and application of a noise prediction tool for the assessment and design of wind turbine airfoils. - Saab Junior, Joseph Youssif (2016)
This report concerns the research, design, implementation and application of an airfoil trailing-edge noise prediction tool in the development of new, quieter airfoil for large-size wind turbine application. The tool is aimed at enabling comparative acoustic performance assessment of airfoils during the early development cycle of new blades and rotors for wind turbine applications. The ultimate goal is to enable the development of quieter wind turbines by the Wind Energy Industry. The task was accomplished by developing software that is simultaneously suitable for comparative design, computationally efficient and user-friendly. The tool was integrated into a state-of-the-art wind turbine design and analysis code that may be downloaded from the web, in compiled or source code form, under general public licensing, at no charge. During the development, an extensive review of the existing airfoil trailing-edge noise prediction models was accomplished, and the semi-empirical BPM model was selected and modified to cope with generic airfoil geometry. The intrinsic accuracy of the original noise prediction model was evaluated as well as its sensitivity to the turbulence length scale parameter, with restrictions imposed accordingly. The criterion allowed comparison of performance of both CFD-RANS and a hybrid solver (XFLR5) on the calculation of the turbulent boundary layer data, with the eventual adjustment and selection of the latter. After all the elements for assembling the method had been selected and the code specified, a collaboration project was made effective between Poli-USP and TU-Berlin, which allowed the seamless coupling of the new airfoil TE noise module, \"PNoise\", to the popular wind turbine design/analysis integrated environment, \"QBlade\". After implementation, the code calculation routines were thoroughly verified and then used in the development of a family of \"silent profiles\" with good relative acoustic and aerodynamic performance. The sample airfoil development study closed the initial design cycle of the new tool and illustrated its ability to fulfill the originally intended purpose of enabling the design of new, quieter blades and rotors for the advancement of the Wind Energy Industry with limited environmental footprint.